2022
DOI: 10.7150/thno.67954
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated microglial activation prevents photoreceptor degeneration by suppressing the accumulation of cell debris and neutrophils in degenerating rat retinas

Abstract: Retinitis pigmentosa initially presents as night blindness owing to defects in rods, and the secondary degeneration of cones ultimately leads to blindness. Previous studies have identified active roles of microglia in the pathogenesis of photoreceptor degeneration in RP. However, the contribution of microglia to photoreceptor degeneration remains controversial, partly due to limited knowledge of microglial phenotypes during RP. Rationale: In this study, we investigated the pathways of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 69 publications
3
7
0
Order By: Relevance
“…TREM2 has been reported to bind lipoproteins, such as ApoE, LDL and CLU/ apoj, which form complexes with Aβ aggregates, facilitating their uptake by microglia [54][55][56]. A group of activated microglial cells with similar gene expression profile was also reported in animal models of retinal degeneration [57]. We observed increased expression of Trem2 and its partner gene Tyrobp at 3 days after RD in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…TREM2 has been reported to bind lipoproteins, such as ApoE, LDL and CLU/ apoj, which form complexes with Aβ aggregates, facilitating their uptake by microglia [54][55][56]. A group of activated microglial cells with similar gene expression profile was also reported in animal models of retinal degeneration [57]. We observed increased expression of Trem2 and its partner gene Tyrobp at 3 days after RD in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, we found that Chx10 + cells increased significantly at the beginning of retinal degeneration in rd10 mice before declining, indicating that the acute response to injury activated the stem cell properties in the retina but failed to repair the retina eventually. In our previous study, we noticed that the microglia phenotype changed according to the development of photoreceptor degeneration in RCS rats 14 . In the present study, the number of Chx10 + cells also fluctuated with microglial clearance and repopulation in the inter group.…”
Section: Discussionmentioning
confidence: 92%
“…However, in mammals, MG show rapid changes in gene expression at the early stage of retina degeneration before a gradual reversion toward a resting state, ultimately gliosis [11]. In our previous studies, microglia are gradually activated into the intermediate stage before being converted to disease-associated microglia, suggesting that there are different subtypes of microglia at the early and late stages of RP [14]. Accordingly, diverse subtypes of microglia seem to play different roles in determining the fate of endogenous stem cells during different phases of injury/degeneration [15].…”
Section: Introductionmentioning
confidence: 93%
“…However, a recent work has challenged this view by indicating a protective effect of microglia on cones in the same mouse model ( 174 ), as suggested by the discussed role of microglia in cone homeostasis ( 111 ). In rats, treatments affecting microglia numbers have resulted in reduced visual function, as a consequence of an increased apoptotic rate in retinal neurons ( 172 , 175 ). Partially explaining this protective role, microglia are not only involved in phagocytosis of stressed photoreceptors, but also in refinement and clearance of improper synaptic connections attempted by bipolar cells with remaining photoreceptors.…”
Section: Roles Of Microglia In Pathologymentioning
confidence: 99%